Roller compaction of moist pharmaceutical powders - Wu, Chuan-Yu; Hung, W.-L.; Miguélez-Morán, Andrés-Miguel; Gururajan, B.; Seville, J. P. K. (International journal of pharmaceutics, 2010)
The compression behaviour of powders during roller compaction is dominated by a number of factors, such as process conditions (roll speed, roll gap, feeding mechanisms and feeding speed) and powder properties (particle size, shape, moisture content). The moisture content affects the powder properties, such as the flowability and cohesion, but it is not clear how the moisture content will influence the powder compression behaviour during roller compaction. In this study, the effect of moisture contents on roller compaction behaviour of microcrystalline cellulose (MCC, Avicel PH102) was investigated experimentally. MCC samples of different moisture contents were prepared by mixing as-received MCC powder with different amount of water that was sprayed onto the powder bed being agitated in a rotary mixer. The flowability of these samples were evaluated in terms of the poured angle of repose and flow functions. The moist powders were then compacted using the instrumented roller compactor developed at the University of Birmingham. The flow and compression behaviour during roller compaction and the properties of produced ribbons were examined. It has been found that, as the moisture content increases, the flowability of moist MCC powders decreases and the powder becomes more cohesive. As a consequence of non-uniform flow of powder into the compaction zone induced by the friction between powder and side cheek plates, all produced ribbons have a higher density in the middle and lower densities at the edges. For the ribbons made of powders with high moisture contents, different hydration states across the ribbon width were also identified from SEM images. Moreover, it was interesting to find that these ribbons were split into two halves. This is attributed to the reduction in the mechanical strength of moist powder compacts with high moisture contents produced at high compression pressures.
Gesehen am 30.04.2024